2000
DOI: 10.7326/0003-4819-132-2-200001180-00003
|View full text |Cite
|
Sign up to set email alerts
|

45-Year Follow-up of Hepatitis C Virus Infection in Healthy Young Adults

Abstract: The rate of HCV infection from 1948 to 1954 among a sample of military recruits parallels that among present-day military recruits and volunteer blood donors. During 45 years of follow-up, HCV-positive persons had low liver-related morbidity and mortality rates. This suggests that healthy HCV-positive persons may be at less risk for progressive liver disease than is currently thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
191
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(209 citation statements)
references
References 29 publications
15
191
1
2
Order By: Relevance
“…In our study, no patient developed cirrhosis after 15 years of infection. Similarly, Seeff et al [12] observed liver disease in only 11.8% of HCV-infected patients after 45 years of infection. In this study, analysis of the causes of mortality after this long period of time revealed that death was attributable to hepatitis C in only 5.9% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no patient developed cirrhosis after 15 years of infection. Similarly, Seeff et al [12] observed liver disease in only 11.8% of HCV-infected patients after 45 years of infection. In this study, analysis of the causes of mortality after this long period of time revealed that death was attributable to hepatitis C in only 5.9% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, testing other specimens stored under less favorable conditions for a longer time still gave the expected 67% RNA detectability in persons with anti-HCV-positivity. 18 Consequently, we believe that the losses of RNA in TTVS are negligible. A recent study of plasmas stored at Ϫ20°C and Ϫ70°C indicates no significant loss.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that 17 samples were positive for anti-HCV antibodies, of which 11 were positive for HCV RNA using PCR. Ten of the 11 PCR-positive samples were classified as subtype 1b but no HCV sequences were reported [20]. Here, we provide partial NS5B sequences from two of these 10 isolates, named US1953a and US1953b (genome positions 7939 -8274 relative to the H77 reference strain).…”
Section: Materials and Methods (A) Archived Hepatitis C Virus Isolatesmentioning
confidence: 99%
“…In previous work, Seeff et al [20] screened for antibodies against HCV more than 8000 archived blood samples that had been obtained between 1948 and 1955 from US military recruits. They reported that 17 samples were positive for anti-HCV antibodies, of which 11 were positive for HCV RNA using PCR.…”
Section: Materials and Methods (A) Archived Hepatitis C Virus Isolatesmentioning
confidence: 99%